2020
DOI: 10.3389/fimmu.2020.551449
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of the Lactobacillus rhamnosus GG Effector Protein HM0539 on Inflammatory Response Through the TLR4/MyD88/NF-кB Axis

Abstract: Inflammatory bowel disease (IBD) is a chronic and relapsing intestinal inflammatory condition with no effective treatment. Probiotics have gained wide attention because of their outstanding advantages in intestinal health issues. In previous studies, a novel soluble protein, HM0539, which is derived from Lactobacillus rhamnosus GG (LGG), showed significant protective effects against murine colitis, but no clear precise mechanism for this effect was provided. In this study, we hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 77 publications
3
37
0
Order By: Relevance
“…Upon ligand binding, MyD88-dependent signaling can result in the phosphorylation of NF-kB, a transcription factor that regulates the levels of IL-1b, IL-6, TNF-a, and several other inflammatory factors, in response to NLRP3 (53,54). Consistent with previous investigations (55,56), our study showed that Kae could inhibit the expression of inflammatory-associated mediators by dampening the activation of the LPS-TLR4-NF-kB signaling in mice with DSStriggered colitis.…”
Section: Discussionsupporting
confidence: 90%
“…Upon ligand binding, MyD88-dependent signaling can result in the phosphorylation of NF-kB, a transcription factor that regulates the levels of IL-1b, IL-6, TNF-a, and several other inflammatory factors, in response to NLRP3 (53,54). Consistent with previous investigations (55,56), our study showed that Kae could inhibit the expression of inflammatory-associated mediators by dampening the activation of the LPS-TLR4-NF-kB signaling in mice with DSStriggered colitis.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, inhibiting TLR4 signaling can effectively regulate the expression levels of inflammatory cytokines induced by DSS. It had been reported that L. rhamnosus GG or L. rhamnosus GG-derived factors could attenuate the inflammatory response induced by activation of TLR4/NF-κB in the colitis [34,35]. In our current research, we found LGG-EVs had the same anti-inflammatory effect, which was accomplished by downregulating the expression of myd88, p65, and p-p65 via inhibiting TLR4 signaling.…”
Section: Discussionsupporting
confidence: 59%
“…TLR4/MYD88/NF-κB signalling pathway plays an important role in the development of RA through the secretion of pro-inflammatory cytokines and matrix metallopeptidase (Kim et al, 2018). The key signalling pathway of TLR4 mediated inflammatory response has been confirmed in the studies of probiotics to improve the inflammation of various diseases (Li et al, 2020;Yu et al, 2020). This study showed that compared with the model group, HG20 could significantly decrease the expression levels of TLR4, MyD88 and NF-κB and IκB-α proteins.…”
Section: Discussionmentioning
confidence: 57%